2019
DOI: 10.1002/stem.3068
|View full text |Cite
|
Sign up to set email alerts
|

SMYD2 Drives Mesendodermal Differentiation of Human Embryonic Stem Cells Through Mediating the Transcriptional Activation of Key Mesendodermal Genes

Abstract: Histone methyltransferases play a critical role in early human development, whereas their roles and precise mechanisms are less understood. SET and MYND domain-containing protein 2 (SMYD2) is a histone lysine methyltransferase induced during early differentiation of human embryonic stem cells (hESCs), but little is known about its function in undifferentiated hESCs and in their early lineage fate decision as well as underlying mechanisms. Here, we explored the role of SMYD2 in the self-renewal and mesendoderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Activation of WNT signaling drives pluripotent stem cell commitment to mesendoderm lineages [40] and is the first step in the differentiation of human pluripotent stem cells (hPSC) to cardiomyocytes in vitro [27,42]. In addition to direct activation of β-Catenin, SMYD2-knockout hPSC lines demonstrated a remarkable reduction of H3K4me1 and H3K36me2 levels at the transcriptional start sites of several signature mesendoderm genes (T, EOMES, MIXL1, and GSC) during differentiation to mesoderm and endoderm [30]. Therefore, we hypothesize that the principal role of SMYD2 in heart development occurs prior to Nkx2.5 expression, which begins 3-4 days after WNT activation via β-Catenin translocation [43].…”
Section: Smyd2 In Embryogenesismentioning
confidence: 99%
“…Activation of WNT signaling drives pluripotent stem cell commitment to mesendoderm lineages [40] and is the first step in the differentiation of human pluripotent stem cells (hPSC) to cardiomyocytes in vitro [27,42]. In addition to direct activation of β-Catenin, SMYD2-knockout hPSC lines demonstrated a remarkable reduction of H3K4me1 and H3K36me2 levels at the transcriptional start sites of several signature mesendoderm genes (T, EOMES, MIXL1, and GSC) during differentiation to mesoderm and endoderm [30]. Therefore, we hypothesize that the principal role of SMYD2 in heart development occurs prior to Nkx2.5 expression, which begins 3-4 days after WNT activation via β-Catenin translocation [43].…”
Section: Smyd2 In Embryogenesismentioning
confidence: 99%
“…Members of the SMYD family are expressed prior to cellular differentiation during preimplantation development [12]; SMYD2 is expressed at the initial transition from the maternal to zygotic program at the 2-4 cell stage [13]. Recently, Bai et al [14] observed that SMYD2 expression during embryo development was significantly enhanced during mesendodermal, Vet. Sci.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the SMYD family are expressed prior to cellular differentiation during preimplantation development [ 12 ]; SMYD2 is expressed at the initial transition from the maternal to zygotic program at the 2–4 cell stage [ 13 ]. Recently, Bai et al [ 14 ] observed that SMYD2 expression during embryo development was significantly enhanced during mesendodermal, pre-endoderm, and mesoderm cells, but not in neuroectodermal differentiation of human embryonic stem (ES) cells. SMYD2 activated transcription factors required for mesendodermal commitment via epigenetic promotion of H3 methylation near their corresponding transcriptional start sites [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our second Featured Article published this month in STEM CELLS Translational Medicine , Li et al describe how transfection with microencapsulated‐modified‐brachyury mRNA can induce MSCs to adopt a cardiopoietic fate that promotes enhanced cardioreparative activity 11 . In a Related Article published recently in STEM CELLS , Bai et al reported how a histone lysine methyltransferase regulates the differentiation of human embryonic stem cells (ESCs) by binding to and altering the chromatin landscape at the regulatory regions of crucial mesendodermal transcription factor genes, including brachyury 12 …”
mentioning
confidence: 99%